AFRICA FOLK MUSIC ATLAS, hardbound book, CD-ROM and 3CD-Audio, edited by Leonardo D'Amico and Francesco Mizzau, 1997, Firenze, Italy: Amharsi Edizioni Multimediali. 93pp. - Thram, Diane (International Library of African Music, 1999)
pages: 195-196
Keywords: African Music